Current understanding of the Trypanosoma cruzi-cardiomyocyte interaction - Calvet, Claudia M.; Melo, Tatiana G.; Garzoni, Luciana R.; Oliveira-Jr, Francisco Odencio R.; Silva Neto, Dayse T.; Meirelles, Maria de Nazareth S.; Pereira, Mirian C. (Frontiers in Immunology, 2012)
Trypanosoma cruzi, the etiological agent of Chagas disease, exhibits multiple strategies to ensure its establishment and persistence in the host. Although this parasite has the ability to infect different organs, heart impairment is the most frequent clinical manifestation of the disease. Advances in knowledge of T. cruzi-cardiomyocyte interactions have contributed to a better understanding of the biological events involved in the pathogenesis of Chagas disease. This brief review focuses on the current understanding of molecules involved in T. cruzi-cardiomyocyte recognition, the mechanism of invasion, and on the effect of intracellular development of T. cruzi on the structural organization and molecular response of the target cell.